Proposed Preventive Maintenance of Air Screw Compressor Machine Using Failure Mode and Effect Analysis and Modularity Design Methods at PT XYZ - Susilo, Dave Dee; Widjajati, Endang Pudji (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Current developments in the industrial world made competition between companies increasingly tight. This required companies to increase the effectiveness and efficiency of their production processes, one of which was by implementing proper machine maintenance so that the machines used could operate well and optimally. PT XYZ is a company engaged in the manufacturing industry which is engaged in making hydrogen peroxide chemical liquid in Indonesia. This company experienced problems with damage to its air screw compressor machine because the maintenance system was carried out when components were damaged, resulting in long downtime. Therefore, this research was carried out with the aim of providing preventive maintenance suggestions using the failure mode and effect analysis (FMEA) method to find critical components of the machine and modularity design to group machine components so as to reduce downtime and minimize maintenance costs. By implementing preventive maintenance with FMEA and modularity design, ten critical sub-components were obtained with a total maintenance cost of IDR 884,839,695, lower than the company's current total maintenance cost of IDR 1,513,836,000. So by applying the proposed method, the company gets an efficiency of 41.55%.